2000
DOI: 10.1016/s0014-5793(00)02229-8
|View full text |Cite
|
Sign up to set email alerts
|

Main ethanol metabolizing alcohol dehydrogenases (ADH I and ADH IV): biochemical functions and the physiological manifestation

Abstract: The range of the biochemical reactions which can be catalyzed by ADH I and ADH IV is extremely wide. The most characterized functions of these enzymes are protection against excess endogenous acetaldehyde, products of lipid peroxidation, exogenous alcohols and some xenobiotics. It was found also that ADH I and ADH IV are important members of the enzyme system synthesizing retinoic acid (especially during embryogenesis). They can oxidize some steroids and participate in bioamine and prostaglandin metabolism but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…11 With a low K m (o5 mM) for ethanol, these enzymes play a major role in ethanol metabolism. There are several polymorphic variants of ADH1, which differ in their efficiency for ethanol oxidation.…”
Section: Ethanol Metabolism: An Updatementioning
confidence: 99%
“…11 With a low K m (o5 mM) for ethanol, these enzymes play a major role in ethanol metabolism. There are several polymorphic variants of ADH1, which differ in their efficiency for ethanol oxidation.…”
Section: Ethanol Metabolism: An Updatementioning
confidence: 99%
“…The best characterised functions of ADH are protection against excess of endogenous alcohols, products of lipid peroxidation and some exogenous xenobiotics [2]. It was also found that isoenzymes of class I ADH participate in bioamine, prostaglandin and retinoid acid metabolism [3]. Moreover class III of ADH catalyses the oxidation of S-hydroxymethylglutathione much more effectively than ethanol [4].…”
Section: Introductionmentioning
confidence: 99%
“…Primarily expressed in the liver [13] , they encode subunits that form a homo-or heterodimer [1] , which accounts for 70% of hepatic ethanol oxidation [14,15] . ADH1B and ADH1C are polymorphic, with three and two alleles [16] , respectively, defined by the amino acids encoded by single nucleotide polymorphisms (SNPs).…”
Section: Metabolic Genesmentioning
confidence: 99%